A Trigonometric sequence (No calculators!)

Geometry Level 3

Evaluate

sin 2 ( 1 ) + sin 2 ( 2 ) + sin 2 ( 3 ) + . . . + sin 2 ( 8 9 ) + sin 2 ( 9 0 ) \sin^2(1^\circ)+\sin^2(2^\circ)+\sin^2(3^\circ)+...+\sin^2(89^\circ)+\sin^2(90^\circ)


The answer is 45.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jul 27, 2017

S = sin 2 1 + sin 2 2 + sin 2 3 + + sin 2 8 9 + sin 2 9 0 = n = 1 90 sin 2 n = 1 2 ( n = 1 90 sin 2 n + n = 1 90 sin 2 n ) = 1 2 ( n = 1 90 sin 2 n + n = 1 90 cos 2 ( 90 n ) ) = 1 2 ( n = 1 90 sin 2 n + n = 0 89 cos 2 n ) = 1 2 ( n = 1 89 ( sin 2 n + cos 2 n ) + sin 9 0 + cos 0 ) = 1 2 ( 89 + 1 + 1 ) = 45.5 \begin{aligned} S & = \sin^2 1^\circ + \sin^2 2^\circ + \sin^2 3^\circ + \cdots + \sin^2 89^\circ + \sin^2 90^\circ \\ & = \sum_{n=1}^{90} \sin^2 n^\circ \\ & = \frac 12 \left(\sum_{n=1}^{90} \sin^2 n^\circ + \sum_{n=1}^{90} \sin^2 n^\circ \right) \\ & = \frac 12 \left(\sum_{\color{#3D99F6}n=1}^{\color{#3D99F6}90} \sin^2 n^\circ + \sum_{\color{#3D99F6}n=1}^{\color{#3D99F6}90} \cos^2 (90- n)^\circ \right) \\ & = \frac 12 \left(\sum_{\color{#3D99F6}n=1}^{\color{#3D99F6}90} \sin^2 n^\circ + \sum_{\color{#D61F06}n=0}^{\color{#D61F06}89} \cos^2 n^\circ \right) \\ & = \frac 12 \left(\sum_{\color{#3D99F6}n=1}^{\color{#D61F06}89} \left(\sin^2 n^\circ + \cos^2 n^\circ\right) + {\color{#3D99F6} \sin 90^\circ} + {\color{#D61F06}\cos 0^\circ} \right) \\ & = \frac 12 \left(89 + {\color{#3D99F6} 1} + {\color{#D61F06}1} \right) = \boxed{45.5} \end{aligned}

Tarmo Taipale
Jul 26, 2017

By sin ( 9 0 x ) = cos x \sin(90^\circ-x)=\cos x we get

sin 2 ( 1 ) + sin 2 ( 2 ) + sin 2 ( 3 ) . . . + sin 2 ( 8 9 ) + sin 2 ( 9 0 ) = sin 2 ( 1 ) + cos 2 ( 1 ) + sin 2 ( 2 ) + cos 2 ( 2 ) + . . . + sin 2 ( 4 4 ) + cos 2 ( 4 4 ) + sin 2 ( 9 0 ) + sin 2 ( 4 5 ) \sin^2(1^\circ)+\sin^2(2^\circ)+\sin^2(3^\circ)...+\sin^2(89^\circ)+\sin^2(90^\circ) = \sin^2(1^\circ)+\cos^2(1^\circ)+\sin^2(2^\circ)+\cos^2(2^\circ)+...+\sin^2(44^\circ)+\cos^2(44^\circ)+\sin^2(90^\circ)+\sin^2(45^\circ)

By sin 2 x + cos 2 x = 1 \sin^2x+\cos^2x=1 , sin 9 0 = 1 \sin 90^\circ = 1 and sin 4 5 = 1 2 \sin 45^\circ = \frac{1}{\sqrt{2}} we get

sin 2 ( 1 ) + cos 2 ( 1 ) + sin 2 ( 2 ) + cos 2 ( 2 ) + . . . + sin 2 ( 4 4 ) + cos 2 ( 4 4 ) + sin 2 ( 9 0 ) + sin 2 ( 4 5 ) = 44 + 1 + 1 2 \sin^2(1^\circ)+\cos^2(1^\circ)+\sin^2(2^\circ)+\cos^2(2^\circ)+...+\sin^2(44^\circ)+\cos^2(44^\circ)+\sin^2(90^\circ)+\sin^2(45^\circ) = 44+1+\frac{1}{2}

44 + 1 + 1 2 = 45.5 44+1+\frac{1}{2}=\boxed{45.5}

Your solution seems perfect but for latex coding i will tell you to use \sin(x) as sine is a function. It will give an output sin ( x ) \sin(x) where your output was s i n ( x ) sin(x) . I think you got the difference.

Md Zuhair - 3 years, 10 months ago

Log in to reply

Yeah I understand, maybe it would look better.

Tarmo Taipale - 3 years, 10 months ago

Log in to reply

Now it's fixed.

Tarmo Taipale - 3 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...